Further on Inequalities for α,h−m-Convex Functions via k-Fractional Integral Operators - Tao Yan (Journal of Mathematics, 2022)
The purpose of this article is to demonstrate new generalized k-fractional Hadamard and Fejér–Hadamard integral inequalities for α,h−m-convex functions. To prove these inequalities, k-fractional integral operators including the generalization of the Mittag–Leffler function are used. The results presented in this article can be considered an important advancement of previously published inequalities.